Your Call Could not be Completed as Dialled: Why Truth Does not Speak to Power In Global Health; Comment on "Knowledge, Moral Claims and the Exercise of Power in Global Health" - Jesse B Bump (Kerman University of Medical Sciences, 2015)
This article contends that legitimacy in the exercise of power comes from the consent of those subject to it. In global health, this implies that the participation of poor country citizens is required for the legitimacy of major actors and institutions. But a review of institutions and processes suggests that this participation is limited or absent. Particularly because of the complex political economy of non-communicable diseases, this participation is essential to the future advancement of global health and the legitimacy of its institutions. More analysis of power and legitimacy provides one entry point for fostering progress.